Determinants of the Dynamics of Malaria Infection Transmission in Mining Areas: Literature Review - Sri Aisyah Nabila; Elvi Sunarsih; Novrikasari Novrikasari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The incidence rate of malaria globally has seen significant fluctuations over the past few years. According to the World Health Organization's World Malaria Report 2023, in 2022, there were an estimated 249 million cases of malaria globally, exceeding the pre-pandemic level of 233 million in 2019 by 16 million cases. Illegal miners are highly vulnerable to malaria due to their work in remote, ecologically disturbed areas, where their activities create breeding grounds for malaria-carrying mosquitoes, significantly increasing their risk of infection. Objective: The aim of this literature review is to find the rsik factors of malaria transmission in arrtisanal mining areas population Method: A PRISMA flow diagram-based has been used to find the most resonant journal research related to malaria transmission in mining areas population. The articles to be analyzed are searched using keywords with Boolean rules such as ("Risk factor" OR "Determinant") AND "Malaria" AND "Transmission" AND ("Mining Area" OR "Mining location"). The chosen papers are the findings of research that meets the objectives and is published in 2020–2024 in English with an international quality Result: Search results from the PubMed, Google Scholar, and ScienceDirect databases yielded 9 articles selected for review published between 2020 to 2024. Research on these articles was conducted in various countries, including Brazil, Venezuela, Indonesia, Gambia, French Guiana (FG), and other countries. A total of 11 articles were carefully reviewed to gather information regarding risk factor of malaria in mining areas in this literature review. Conclusion: Improving knowledge, healthcare access, and preventive practices is essential to reducing malaria transmission in high-risk m